The Compliance Degree of Listed Banks in the Saudi Capital Market with the Requirements of Presentation and Disclosure of Islamic Sharia in Annual Financial Reports: An Empirical Study - Alsaadi, عبدالله (Journal of King Abdulaziz University: Islamic Economics, 2024)
This research aims to study the general framework for compliance with Sharia, and to identify its requirements in light of the additions to International Accounting Standard No. (1) (Presentation of Financial Statements), as well as identifying the responsibility of management towards these requirements. In particular, this study seeks to identify the level of compliance with the presentation and disclosure requirements of Sharia in financial reports. The sample comprises ten banks domiciled in Saudi Arabia for the period from 2017 to 2020. Based on the content analysis, the empirical results show that, in general, the level of banks’ compliance with the presentation and disclosure requirements of Sharia in financial reports is quite low, the results of the regression analysis show that there is no relationship between the indicator of disclosure of Sharia compliance requirements and the factors influencing it (bank size, ownership, and financial performance). This study recommends that there should be cooperation between the Saudi Organization of Auditors and Accountants and the Central Bank of Saudi Arabia in order to issue a guideline that can assist to increase the awareness amongst banks about the importance of compliance with the requirements of Sharia in financial reporting. Moreover, banks, and particularly those in charge of governance and auditors in banks, should be encouraged to raise the level of Sharia compliance requirements in the financial report.